Finite element model predicts the biomechanical performance of transforaminal lumbar interbody fusion with various porous additive manufactured cages. (1st April 2018) - Zhang, Zhenjun; Li, Hui; Fogel, Guy R.; Xiang, Dingding; Liao, Zhenhua; Liu, Weiqiang
Abstract: In lumbar interbody fusion, a porous additive manufactured (AM) cage can provide more desirable stiffness, and may be beneficial to bone ingrowth. The biomechanical influence of porous cages on stability, subsidence, and facet contact force has not been fully described. The aim of this study was to verify biomechanical effects of porous cages. A surgical finite element (FE) model of transforaminal lumbar interbody fusion (TLIF) was constructed. Partially porous (PP) cages and fully porous (FP) cages were applied. Mechanical tests were performed to obtain the mechanical parameters of porous materials. The porous cages were compared to solid titanium (TI) cage and solid PEEK cage. Four motion modes were simulated. Range of motion (ROM), cage stress, endplate stress, and facet joint force (FJF) were compared. After interbody fusion, ROM decreased by more than 90% in flexion, bending and rotation. Compared with TI and PP cages, PEEK and FP cages substantially reduced the maximum stresses in cage and endplate in all motion modes. Compared with PEEK cages, the stresses in cage and endplate for FP cages decreased, whereas the ROM increased. Compared among three FP cages, the stresses in cage and endplate decreased with increasing porosity, whereas ROM increased with increasing porosity. FJF for various cages was substantially reduced compared to the intact model in all motion modes except for flexion. In summary, fully porous cages with a porosity of between 65% and 80% may offer an alternative to solid PEEK cages in TLIF.